HUBUNGAN PENGHASILAN DENGAN KINERJA PEDAGOGIK GURU DI TAMAN KANAK- KANAK KECAMATAN SUNGAI RAYA. - Restu Ridha Amalia; Aunurrahman Aunurrahman; Dian Miranda (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2022)
This research is a quantitative research with a correlational approach. The population of the study was Kindergarten teachers in Sungai Raya District, a total of 30 people. Furthermore, data collection techniques using questionnaires and observation. Test the validity of the research instrument using product moment correlation and reliability testing. Analysis of the data used in the form of simple regression analysis to answer the formulation of the problem. The results showed that the income of teachers in Kindergarten in Sungai Raya District was still low. Meanwhile, the teacher's performance in Kindergarten in Sungai Raya District in learning is in the Very Good and Good categories. The results of the regression analysis show that there is a relationship between income and teacher pedagogic performance in Kindergarten, Sungai Raya District, which is indicated by Y = 21.789 + 0.579X or teacher performance = 21.789 + 0.579 income. For every increase in one unit of income, the teacher's performance will increase by 21.789 + 0.579. And income contributes to the pedagogic performance of teachers in learning by 11.4%.